Exprerimental Evaluation of a Dedicated Pinhole SPECT System for Small Animal Imaging and Scintimammography - David, S.; Georgiou, M.; Fysikopoulos, E.; Loudos, G. (Engineering, Technology & Applied Science Research, 2011)
Nuclear medicine (SPECT and PET) provides functional information, which is complementary to the structural. In cancer imaging radiopharmaceuticals allow visualization of cancer cells functionality, thus small cell population can be imaged. This allows early diagnosis, as well as fast assessment of response to therapy. Our system is a single head gamma camera based on an R3292 position sensitive photomultiplier tube (PSPMT), coupled to a 10cm in diameter CsI:Tl crystal. We have assessed two CsI:Tl crystals with pixel size of 2x2mm2 and 3x3mm2 respectively. Three collimators were tested: a) a hexagonal, 1.1mm in diameter, general purpose parallel hole collimator b) a 1mm pinhole and c) a 2mm pinhole. Systems were tested using capillary phantoms. All measurements were carried out in photon counting mode with gamma radiation produced by 99mTc. Using the 2x2mm2 crystal and the 1mm pinhole collimator - a resolution better than 1mm was achieved. This allows very detailed imaging of small animals. Using the 3x3mm2 and the 2mm pinhole collimator a resolution of 1.3mm was possible with suitable sensitivity for breast imaging. Those results indicate that this system is suitable for animal and breast studies. The next step will be clinical evaluation of the camera.